The marine algae Sargassum spp. (Sargassaceae) as feed for sheep in tropical and subtropical regions - Marín, Alejandro (2009)
The objective of this study was to evaluate Sargassum meal as feed for sheep through the measures of in vivo digestibility, dry matter degradability, pH, ammonia and volatile fatty acids in rumen. The Sargassum algae used in this experiment were collected at the end of spring, when they are more abundant, bigger, and have completed their reproductive cycle. Four tons (wet weigth) were collected manually from the intertidal zone of La Paz bay, Baja California Sur, Mexico. These algae were sun-dried and ground in a hammer mill to obtain the Sargassum meal. Four fistulated Pelibuey sheep, were fed daily with diets containing the marine algae (MA) at different levels (0, 10, 20 and 30 %), using a 4 x 4 Latin-square design experiment. Feed intake was not affected (p > 0.05). Water consumption and urine excretion increased with MA (p < 0.05; r2=0.54 and r2=0.74, respectively). In all treatments dry matter digestibility was of 74%-79%, and crude protein digestibility was of 85%-88%. Acid detergent fiber (59%-65%) and neutral detergent fiber (55%-66%) digestibility were greater in all treatments with MA. Ruminal pH was greater in all groups fed with MA (p < 0.05). Ammonium concentration was not influenced (p > 0.05) by MA. Ruminal volatile fatty acids decreased in all MA groups (p < 0.05). The marine algae Sargassum spp. can be used as a feed supplement for sheep, especially in tropical and subtropical regions where these marine algae are available.